Case report: Successful treatment of refractory membranous nephropathy with telitacicept - Zhang, Lei; Jin, Hua; Wang, Dong; Wang, Yiping (Frontiers in Immunology, 2023)
Despite various treatment methods, the remission rate of membranous nephropathy remains limited. Refractory membranous nephropathy especially lacks effective treatment plans. Telitacicept achieves comprehensive inhibition of CD20-positive B cells, plasma cells, and T cells, thereby bringing new hope to the treatment of membranous nephropathy and refractory membranous nephropathy.Here, we report a case of a 46-year-old man with membranous nephropathy. Although the combined treatment with glucocorticoid, tacrolimus, mycophenolate mofetil, cyclophosphamide, and rituximab was not successful, the patient achieved complete remission of urinary protein after glucocorticoid combined with telitacicept. This is the first report on the application of telitacicept in the treatment of membranous nephropathy, especially refractory membranous nephropathy. The application of telitacicept in the treatment of membranous nephropathy deserves further attention.